Groundwater: Focusing on the Real Issue - Gisser, Micha (Journal of Political Economy, 1983)
Most studies of the welfare economics of groundwater have focused mainly on the dichotomy between optimal control of groundwater use and no control at all. This article argues that, under circumstances that generally prevail in semiarid zones, assigning property rights to groundwater and permitting the market to determine the allocation of water use can lead to a second-best solution. An argument is made that if potential users would be allowed to Coase-bargain with incumbent users on the issuance of new groundwater rights, the second-best solution is elevated to a Pareto-optimal solution. This article is also a tale of two states: water law and performance in New Mexico and Arizona.